Health behaviors in the field of breast cancer prevention among patients - Paweł Kalinowski; Urszula Bojakowska; Marta Estera Kowalska (Journal of Education, Health and Sport, 2018)
Introduction Breast cancer is the most frequent malignant disease in women all over the world: it accounts for 25.1% of all cancer cases. The major problem connected with this cancer is late diagnosis which is reflected in high mortality rates. Therefore, education is recommended in all countries with a view to increasing health awareness of women. Objective of the study The objective of the study was a retrospective analysis of health behaviour concerning breast cancer prevention in a group of patients with the malignant breast disease. The analysis was carried out with respect to education, place of residence and financial status of the surveyed women. Material and method The research was carried out by means of a diagnostic survey. The instrument used was an original questionnaire designed for the purposes of the study. A total of 200 female breast cancer patients were surveyed between September 2015 and April 2016. The data collected in the study were subjected to statistical analysis. Result and conclusions The research demonstrated that, irrespective of an education level, place of residence and financial status, lack of interest in preventive actions aimed at early diagnosis of breast cancer could be observed. Therefore, health awareness of women in this respect should be increased.